2016
DOI: 10.1179/2151090315y.0000000004
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the signs and symptoms of temporomandibular disorder in females by using the ProTMDMulti protocol and the visual analog scale before and after acupuncture treatment

Abstract: For TMDs with joint components, the best acupuncture treatment involves local points and for the TMDs with muscle components, points at a distance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
8
0
2
Order By: Relevance
“…feminine gender. 6,7,11 The patient of this study fits this age range and gender, and the proposed therapy was planned for painful symptomatology remission. 3,11,12 Chronic pain is a great burden to society, responsible for personal suffering, drug abuse, and a considerable financial problem due to treatment spending and lost productivity.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…feminine gender. 6,7,11 The patient of this study fits this age range and gender, and the proposed therapy was planned for painful symptomatology remission. 3,11,12 Chronic pain is a great burden to society, responsible for personal suffering, drug abuse, and a considerable financial problem due to treatment spending and lost productivity.…”
Section: Discussionmentioning
confidence: 95%
“…6,7,11 The patient of this study fits this age range and gender, and the proposed therapy was planned for painful symptomatology remission. 3,11,12 Chronic pain is a great burden to society, responsible for personal suffering, drug abuse, and a considerable financial problem due to treatment spending and lost productivity. 10 A study from 2012 found that the annual cost of pain in the United States ranged from $560 to $635 billion dollars, being superior to the costs of heart disease ($309 billion), cancer ($243 billion), and diabetes ($188 billion).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Ademais, a Odontologia possui inúmeros resultados benéficos sobre acupuntura: estudos sobre analgesia por acupuntura na redução da intensidade da dor dentária aguda [29]; para Disfunção Temporomandibular (DTM) com componentes articulares, o melhor tratamento com acupuntura envolve pontos locais e para os DTM com componentes musculares, pontos à distância [30]; aplicação do estimulador neuromagnético Haihua modelo CD-9, utilizado dentro dos preceitos da acupuntura no tratamento de sintomas de dor relacionada à DTM [31]; com parestesia do nervo alveolar inferior e dor causada por uma cirurgia de implante realizada há dois anos [32]; em pacientes com neuralgia trigeminal idiopática apenas o grupo de acupuntura manteve seu efeito analgésico por 6 meses [33].…”
Section: Snv1unclassified
“…Em relação à percepção da severidade dos sinais e sintomas de DTM, avaliada pelo protocolo ProDTMmulti parte II, antes do tratamento (FD) todos os grupos com DTM apresentaram escores parciais e total significantemente maiores que do grupo controle, como previamente observado em estudos, nos quais o mesmo questionário foi empregado, na íntegra (Felício et al, 2010;Felício et al, 2012a;Ferreira et al, 2014), ou parcialmente Branco et al, 2015), exceto para dificuldade para engolir.…”
Section: Tomados Em Conjunto Os Resultados Atuais Indicam Que O Protunclassified